2013
DOI: 10.3233/jid-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Smartphones as Learning Technology in a Korean University

Abstract: iPhone and Android technology only became available in Korea in 2010, yet today, nearly every student in Korea's top university carries either an iPhone or Android enabled phone. Students are plugged in and communicating constantly. One Lifelong Learning class 1 investigated the use of smartphones among Education and Engineering students. Both the process of the class and the outcomes of the research reveal much of how the practices of learning are changing in a dynamic, globally-linked university. Their answe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
(3 reference statements)
0
14
0
1
Order By: Relevance
“…For example, although some studies like Bomhold (2013) found that students did use their mobile devices for academic activities, other researchers (Alfawareh & Jusoh, 2014;Gupta & Manjrekar, 2012) had an opposite finding, i.e., they found out that students seldom used their mobile devices for learning and studying. Kim, Ilon, and Altmann (2013) even reported that those heavy users of mobile device have been are usually not the most intensive engaged m-learning users. Based on the autonomy feature of m-learning which that allows learners to take charge of their own learning progress (Liu et al, 2010;Sarrab, Al-Shihi, & Hussain Rehman, 2013), it is generally agreed that m-learning is more suitable for self-regulated learning (Liu et al, 2010;Park & Jung, 2013).…”
Section: Literature Review On M-learning Overviewmentioning
confidence: 99%
“…For example, although some studies like Bomhold (2013) found that students did use their mobile devices for academic activities, other researchers (Alfawareh & Jusoh, 2014;Gupta & Manjrekar, 2012) had an opposite finding, i.e., they found out that students seldom used their mobile devices for learning and studying. Kim, Ilon, and Altmann (2013) even reported that those heavy users of mobile device have been are usually not the most intensive engaged m-learning users. Based on the autonomy feature of m-learning which that allows learners to take charge of their own learning progress (Liu et al, 2010;Sarrab, Al-Shihi, & Hussain Rehman, 2013), it is generally agreed that m-learning is more suitable for self-regulated learning (Liu et al, 2010;Park & Jung, 2013).…”
Section: Literature Review On M-learning Overviewmentioning
confidence: 99%
“…Students used smartphones for sharing notes between classmates, recording lectures, as well as taking pictures of assignments for future reference and sharing exam results on a Facebook through their smartphones. Kim and Altmann (2013) also found that generally each student had 80 applications on his/her Smartphone, and 16% of the applications were used for some kind of learning. Moreover, Payne et al (2012) explored the usage of smartphones among medical students in the United Kingdom and found a high level of Smartphone ownership and participants endorsed the development of more applications to support medical students.…”
Section: Literature Backgroundmentioning
confidence: 96%
“…While advances in hardware usually get the most attention, Godwin-Jones (2011) mentions the equal importance of software and the new opportunities that arise from mobile application development. Recently there have been some studies focusing on how mobile apps are used and perceived by learners (Kim, Ilon, & Altmann, 2013;Steel, 2012), and some studies have also commented on app development and design (Kukulska-Hulme et al, 2011). Clearly MALL is an exciting area of research with many discoveries ahead.…”
Section: Literature Reviewmentioning
confidence: 99%